Non-regression in international environmental law : human rights doctrine and the promises of comparative international law / Markus Vordermayer-Riemer. - Vordermayer-Riemer, Markus (Intersentia, 2020)
The book analyses the emerging concept of 'non-regression' as a novel legal principle of international environmental law. It traces the development of non-regression in the context of international human rights law and provides an examination of the respective jurisprudence under universal and regional human rights instruments. These are then compared to closely-related normative concepts in the framework of international environmental law, including the Paris Climate Change Agreement and biodiversity-related agreements such as the Ramsar Convention on Wetlands and the Bonn Convention on Migratory Species. The book advocates an innovative usage of comparative law methods in order to enable fruitful interactions between human rights and international environmental law. Non-Regression in International Environmental Law is an important contribution to the development of international environmental law that offers a fresh perspective on the relationship between human rights and international environmental law. DR MARKUS VORDERMAYER-RIEMER is a legal and policy officer at the Bavarian State Ministry of the Environment and Consumer Protection, Germany. He was previously a law clerk at the Higher Regional Court of Munich, Germany. He has also worked as a research assistant at the Institute of International Law of Ludwig-Maximilian-University, Munich, and was educated in both civil law and common law jurisdictions.